Isolation and Identification of Microbes from Mobile Phones in Orthopedic Operation Theatre - Shehla Umbreen, Abdul Rasheed, Shumaila Jabbar, Faheem Mubashir Farooqi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Post-operative infection in orthopedic surgery is an emerging problem for the orthopedic surgeons and patients. Mobile phones are the most common object brought in theatre by the health professionals and are contaminated by different strains of bacteria which may be the cause of surgical site infection. Objective: To isolate and identify the microbes on the surface of the mobile phones of the hospital staff in orthopedic operation theatre. Methods: Samples were taken from the mobile phones of the health care professionals (Surgeons, assistants, Anesthetists, Staff nurses and paramedical staff) entering the operation theatre of the LIHAS (Lahore Institute of Hand and Arm Surgery). All the samples were taken using the culture swab sticks on both sides of the mobile phones of the health care staff of operation theatre on the same day. Results: The total numbers of mobile phone sampled were 45. 97.3% of the cell phones were contaminated with one or more bacteria and the most common bacteria isolated was Staphylococcus Epidermidis (62.22%) followed by Staphylococcus Aureus (42.2%), Micrococcus (37.77%), Bacillus (33.33%), E.Coli (31.11%), Pseudomonas Aerugonosa (22.22%) and others including Proteus Mirabilis, Enterobacter and Acinetobacter Baumannii (8.88%). Conclusion: It is concluded that the mobile phone can be the major source of contamination in operation theatre, so the use of mobile phone in the theatre should be minimized and should encourage to clean the phone regularly.